Tourism and Lifestyles: Analysis of Cross-Cultural Interface - Sharma, Ramji (Himalayan Journal of Sociology and Anthropology, 2011)
Tourism has emerged as one of the largest industries in terms of income generation and employment opportunities around the globe. It seems that none of the settlements on earth can preserve their isolation today merely due to the inlux of globalization. Tourism has been established as a striking by-product of globalization. Due to its economic upshots on foreign currency earning without actually sending any tangible products out of the boarder, almost all the countries around the globe have begun to consign a high priority to its development. However, its effects and implications appear in numerous faces and facades both with momentary and enduring bearings - some with afirmative consignments and other with negative provocations. From socio-cultural dimension, tourism appears as a vehicle of cross-cultural interface resulting socio-cultural phenomena like diffusion, integration, acculturation and assimilation. Its apparent effects can be seen in every host society with different tangs and textures. The lifestyle of the people of tourist receiving community can not remain in isolation. This study analyzes the impacts caused by the development of tourism business over the lifestyles of the people of host societies viz. catchments of Fewa Lake of Pokhara and Sarangkot of Kaski, Nepal. DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4675 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 206-223